(أحكام صيام المسنين (دراسة فقهية مقارنة : Ahkam of Fasting for the Elderly (Comparative Legal Study) - Andi Indra Putri; Nuraeni Novira; Bahtiar Bahri Mappoleang (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Acts of worship required by the Shari'a are not limited to certain groups of people without any other group. It is an obligation that binds every Muslim as long as he still has the status of a mukallaf and has the ability. The reality that exists demands to understand ahkam related to elderly people because there is hardly a single house in the middle of the Muslims except in which there are elderly people. This study aims to describe ahkam regarding elderly people concerning fasting and fidyah, as it aims to discuss the law of changing his fast after he dies. This research focuses on examining the fasting ahkam for elderly people based on the interpretation of jurisprudence, then analyzing and judging the shar'i law of each problem after deciphering the root causes and causes by describing the opinions of each ulama and their arguments on each of these issues. In this study, researchers used descriptive analysis methods, and have come to several important conclusions from the results of the study, the most important of which is that fasting is a Shari'a command that is required of parents as long as two conditions are met, namely being intelligent and capable. Relief is only given to parents based on the provisions of the Shari'a. If he is unable to fast, then by paying fidyah without having to fast, and for his heirs to change his fast if he dies as a form of devotion and good deeds to him.